PENGARUH PEMBERIAN PUPUK DAUN BAYFOLAN TERHADAP PERTUMBUHAN BIBIT GMELINA (Gmelina arborea Roxb.) - Risal Umalekhoa; Euis F.S. Pangemanan; Semuel P. Ratag (COCOS, 2017)
ABSTRACTGmelina (Gmelina arborea Roxb.) Is a genus of the family Verbenaceae, Gmelina includes 33 types of one species of them (Gmelina arborea Roxb.) Foliar fertilizer Bayfolan a macro and micro inorganic fertilizers, liquid complete. This study aimed to determine the effect of foliar fertilizer on the growth of seedlings Bayfolan (Gmelina arborea Roxb) using complete randomized design (CRD), with 5 treatments and 5 replications. Each treatment consists of one plant. Seedlings in use amounted to 25 seeds (Gmelina arborea Roxb.). Treatment A as the control (0 ml bayfola / liter of water) treatment B, (2 ml bayfolan / liter of water) treatment C, (3 ml bayfolan / liter of water) treatment D, (4 ml bayfolan / liter of water) treatment E , (5 ml bayfolan / liter of water). The media used are soil, sand and chicken manure, with a ratio of 1: 1: 1. The variables observed were the increase of plant height and the increase of leaf number. The results showed that bayfolan leaf fertilizer did not affect nyta, on the increase of height and amount of leaf of Gmelina seedlingsKeywords: Gmelina (Gmelina arborea Roxb) Bayfolan Leaf Fertilizer